2006
DOI: 10.1111/j.1442-9071.2006.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal objective perimetry compared with Humphrey full‐threshold perimetry in patients with optic neuritis

Abstract: The mfVEP detected more abnormalities in patients with ON than HVF perimetry. The use of latency recordings as well as combined amplitude and asymmetry plots is advantageous and has the potential to detect abnormalities not otherwise detected on HVF perimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…This substantially reduces intersubject variability and allows more reliable comparison with a normal database for applying mfVEP in the detection of visual field changes clinically. 12 A number of studies have shown that AccuMap mfVEP can provide a good measurement of visual field defects in glaucomatous optic neuropathy, 5,13-15 optic neuritis, 7,16 compressive optic neuropathy, 6 and other conditions. [17][18][19] Strong correlation has been observed between areas of visual field loss on Humphrey subjective perimetry and mfVEP amplitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This substantially reduces intersubject variability and allows more reliable comparison with a normal database for applying mfVEP in the detection of visual field changes clinically. 12 A number of studies have shown that AccuMap mfVEP can provide a good measurement of visual field defects in glaucomatous optic neuropathy, 5,13-15 optic neuritis, 7,16 compressive optic neuropathy, 6 and other conditions. [17][18][19] Strong correlation has been observed between areas of visual field loss on Humphrey subjective perimetry and mfVEP amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…An AccuMap Severity Index (ASI) score was also displayed based on the total number of abnormal zones, relative severity, and asymmetry. By comparing the results with a built-in normative database of 100 patients, the ASI was classified as normal (within 95% confidence interval (CI), ASI 0-11), borderline (95-99% CI, ASI [11][12][13][14][15][16][17][18][19], or outside normal limits (outside 99% CI, ASI419).…”
Section: Methodsmentioning
confidence: 99%
“…They found a comparable amplitude loss of mfVEP response in region with bitemporal visual defect. Several studies in non-glaucomatous optic neuropathy [38][39][40] and in glaucomatous optic neuropathy [32,[41][42][43] have also shown that correspondence exists between visual field defect determined by perimetry and the reduction of mfVEP amplitude. Latencies were non-recordable (gray circles in column 5 and 6 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[343738394041] In this study, we have analyzed the size of the amplitude reduction and its pattern in mfVEP topographical amplitude deviation map among optic nerve disorders using the visual field profile classification of ONTT as shown in Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…Pakrou et al .,[43] reported that only 8.3% of the 16 optic neuritis subjects showed a central or centrocecal mfVEP defect using cluster criteria. Laron et al .,[37] analyzed the mfVEP amplitude and latency abnormality using cluster criteria in MS-ON eyes. They reported that although abnormal sectors were diffusely distributed, the central 10° was more affected than periphery.…”
Section: Discussionmentioning
confidence: 99%